Isolation and identification of microflora involved in tapai, a Sabah's fermented alcoholic beverage - Chiang, Yong Wee (2008)
Tapai is an indigenous fermented alcoholic beverage of Kadazan, Dusun and Murut ethnics in Sabah, yet little research has been done on this beverage. The objective of this study was to identify the microflora involved in tapai fermentation as well as to determine the physicochemical changes and proximate changes during the fermentation. Freshly prepared samples were obtained and kept at similar conditions through fermentation before withdrawn for microbiological and chemical analysis at each interval times. The alcohol content, pH, titratable acidity (as %lactic acid) and total soluble solids of the tapai were 12.3±0.97%, 4.0±0.17,0.82±0.03% and 14°Brix, respectively at the end process of tapai fermentation. The moisture, ash, protein, crude fiber and carbohydrate content increased significantly (p<0.05) during fermentation whereas during 12 months of storage, only protein content showed significant changes (p>0.05). Aerobic mesophilies, yeast and lactic acid bacteria count increased in the early stage of fermentation but decreased thereafter until the end of the fermentation process. The yeasts were the only flora detected after 12 months of storage. Mould and Enterobacteriaceae were not detected on the 4th day of the fermentation and thereafter. A total of 102 yeasts were isolated, consisting of Candida utilis, Candida krusei, Candida famata, Candida pelliculosa, Candida glabrata, Candida sphaerica biotype 1, Saccharomyces cerevisiae biotype 1, Saccharomyces cerevisiae biotype 2, Rhodotorula mucilaginosa biotype 2, Rhodotorula glutinis and Cryptococcus laurentii. The mould identified was Mucor circinelloides. There were 116 lactic acid bacteria isolated, including Pediococcus pentosaceus biotype 1, Lactobacillusp lantarum biotype 1, Lactobacillus paracaseis sp. paracasei biotype 3 and Lactobacillusb revis biotype 3. Only C. utilis and the unidentified mould showed amylolytic and proteolytic properties. The fermentation process of tapai was found initiated by non-Saccharomyces yeast and P. pentosaceus biotype 1, then replaced by Saccharomyces yeasts and Lactobacilluss pp. in the later stage of fermentation. It is envisaged that identification of roles and potentials of the different isolates in controlled fermentation of tapai would help the production of starter culture that produce superior quality tapai. Additional studies using polyphasic approaches could be carried out for analysis of microbial dynamics in tapai fermentation